Improving the legal basis of rapid search activities in Uzbekistan is a priority - Gafurov Farkhod Rashidovich (Zien Journals, 2022)
This scientific article describes the issues of improving the organizational and legal basis of search and rescue operations in the Republic of Uzbekistan. Also, problems encountered in the field of rapid search operations and proposals for their solution are described
Keywords: operational-search activity; operational-search activities; operational officer